Vaginal dryness in primary Sjögren's syndrome: a histopathological case–control study. (11th February 2020) - van Nimwegen, Jolien F; van der Tuuk, Karin; Liefers, Silvia C; Verstappen, Gwenny M; Visser, Annie; Wijnsma, Robin F; Vissink, Arjan; Hollema, Harry; Mourits, Marian J E; Bootsma, Hendrika; Kroese, Frans G M
Abstract: Objective: The aim was to study clinical, histopathological and immunological changes in the vagina and cervix of women with primary SS, which might explain vaginal dryness. Methods: We included 10 pre-menopausal female primary SS patients with vaginal dryness and 10 pre-menopausal controls undergoing a laparoscopic procedure. The vaginal health index was recorded. Multiplex immunoassays and flow cytometry were performed on endocervical swab and cervicovaginal lavage samples to evaluate cellular and soluble immune markers. Mid-vaginal and endocervical biopsies were taken and stained for various leucocyte markers, caldesmon (smooth muscle cells), avian V-ets erythroblastosis virus E26 oncogene homologue (ERG; endothelial cells) and anti-podoplanin (lymphatic endothelium). The number of positive pixels per square micrometre was calculated. Results: One patient was excluded because of Clamydia trachomatis, and two controls were excluded because of endometriosis observed during their laparoscopy. Vaginal health was impaired in primary SS. CD45 + cells were increased in vaginal biopsies of women with primary SS compared with controls. Infiltrates were predominantly located in the peri-epithelial region, and mostly consisted of CD3 + lymphocytes. In the endocervix, CD45 + infiltrates were present in patients and in controls, but a higher number of B lymphocytes was seen in primary SS. Vascular smooth muscle cells were decreased in the vagina of primary SS patients. No differences were found in leucocyte subsets in the vaginal and endocervical lumen. CXCL10 was increased in endocervical swab samples of primary SS patients. Conclusion: Women with primary SS show impaired vaginal health and increased lymphocytic infiltration in the vagina compared with controls. Vaginal dryness in primary SS might be caused by vascular dysfunction, possibly induced by IFN-mediated pathways.